An??lise do desenvolvimento neuropsicomotor em crian??as nascidas prematuras e com baixo peso - Prado, Ivanete Fernandes do (2018)
This study aimed to analyze neuropsychomotor development in children born premature and underweight accompanied at the Family Health Units of the city of Guanambi Bahia, through the Denver Development Screening Test II. This is a cross-sectional study with a control-case design, approved by the Research Ethics Committee of the Catholic University of Bras??lia and the Health Secretariat of the State of Bahia under opinion n?? 913.952. After the previous experimentation of data collection instruments in a pilot study, the evaluation of children aged between zero and six years was started, accompanied by the Family Health Units (Caso Group) and Casa da Crian??a (Control Group). Data analysis was done using frequency distribution tables, chi-square test and Fisher's Exact and logistic regression. The sample consisted of 85 children, 55.3% (n = 47) of the case group and 44.7% (n = 38) of the control group. The individual analysis showed a significant association between the groups and the gestational age, birth weight, type of delivery, hospitalization and place of residence. There was also a significant association between the groups and the father's income, the age and the schooling of the mother. There was a higher percentage of cesarean delivery, of children who were hospitalized, of older mothers and a higher educational level in the case group, and a higher percentage of parents with income up to a minimum wage in the control group. In the case group, a greater percentage of delays and cautions were found in the individual items in the area of language and personal-social and in the control group in the area of language and motor-fine-adaptive. There was no statistically significant difference in the four areas in relation to the result of the individual items between the groups. Of the total number of children, 14.1% presented questionable results in Denver II, 21.3% of the children in the case group and 5.3% of the children in the control group. Children who were hospitalized and mothers with lower education were 18.52 and 8.57 times more likely to present questionable results in Denver II, respectively. In the multiple analysis, the groups showed no significant association with neuropsychomotor development. Only the child's hospitalization and the mother's schooling had a significant association with neuropsychomotor development. The importance of monitoring neuropsychomotor development in children born premature and / or underweight is highlighted. This will minimize the damage that possible delays and cautions can bring to the future life and signal the need for early intervention in specific cases where developmental delays have been identified. It is also recommended the guidance of mothers and / or caregivers on the importance of physical activity in stimulating child development.